Evaluation of Coordinate Position Precision Using GNSS NEO SERIES and GSM SIM 7000E Modules - Kusuma, Hollanda Arief; Irnawati, Yunita; Aflaha, Fadli Aulia; Baihaque, Muhd. Ridho (Journal of Applied Geospatial Information, 2024)
This study investigates the precision of coordinate positioning using Global Navigation Satellite System (GNSS) technology, focusing on GNSS Neo Series modules and the GSM SIM 7000E module. The research aims to address the lack of comparative studies evaluating these GNSS receivers simultaneously. A field test spanning 24 hours was conducted to collect data on satellite acquisition and Horizontal Dilution of Precision (HDOP). The GNSS systems were deployed in a controlled environment at the Class I Meteorological Station Hang Nadim, Batam. The system developed comprised GNSS modules (Neo 6M, Neo 7M, Neo 8M, and GSM SIM 7000E), an ESP32 microcontroller, Arduino UNO, and a Micro SD shield module. Data processing involved converting coordinates to meters and calculating longitude and latitude errors. Root Mean Square Error (RMSE) analysis and one-way ANOVA were performed to assess accuracy and compare the GNSS receivers. Results indicate that the GSM SIM 7000E demonstrated superior satellite acquisition, leading to higher accuracy in coordinate positioning compared to the Neo Series modules. The study also identified optimal data collection times for accurate dispersion. These findings provide valuable insights into selecting and deploying GNSS receivers, enhancing performance in location-based services and scientific applications.